Lamb wave inspection using piezoelectric diaphragms: An initial feasibility study - Campeiro, Leandro Melo [UNESP]; Budoya, Danilo Ecidir [UNESP]; Baptista, Fabricio Guimarães [UNESP] (Elsevier, 2021)
Lamb wave-based inspection has been extensively investigated and reported in the literature as a non-destructive technique in structural health monitoring and other applications. The generation and reception of Lamb waves are typically performed with piezoelectric ceramics operating as actuators and sensors, respectively. This article presents a study of the feasibility of piezoelectric diaphragms as an alternative transducer, allowing to expand the research as well as to accelerate the implementation of Lamb wave-based SHM systems with lower installation costs. Piezoelectric diaphragms are sound components widely used in everyday electronic devices and, in addition to the low cost, they have the advantage of being mass-produced by different manufacturers in standard sizes and are readily available. To assess the feasibility of these components, basic analysis by finite element method (FEM) and experimental tests were carried out on aluminum plates and the results obtained with the diaphragms were compared with those obtained using conventional piezoelectric ceramics. Structural damage was simulated by making cracks and drilling holes in the structure and an imaging algorithm together with damage index based on the wavelet transform was used to detect and locate damage. In addition, tests were carried out to evaluate and compare the reproducibility of the results and the effects of temperature variation on the two types of transducers. FEM and experimental results show that piezoelectric diaphragms are feasible for generating and receiving Lamb waves, as well as detecting structural damage. Therefore, these commercial sound components can also be alternative transducers for applications involving Lamb waves.
Keywords: Damage detection; Lamb waves; Non-destructive testing; Piezoelectric diaphragms; SHM